2022
DOI: 10.1073/pnas.2200477119
|View full text |Cite
|
Sign up to set email alerts
|

IGF2BP2 promotes cancer progression by degrading the RNA transcript encoding a v-ATPase subunit

Abstract: IGF2BP2 binds to a number of RNA transcripts and has been suggested to function as a tumor promoter, although little is known regarding the mechanisms that regulate its roles in RNA metabolism. Here we demonstrate that IGF2BP2 binds to the 3′ untranslated region of the transcript encoding ATP6V1A, a catalytic subunit of the vacuolar ATPase (v-ATPase), and serves as a substrate for the NAD + -dependent deacetylase SIRT1, which regulates how IGF2BP2 affects the stability of the ATP6V1A tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…IGF2BP2 has been proposed as a tumor promoter and shown to affect many cancer hallmarks through positive or negative regulation of its target genes. A recent study demonstrated that IGF2BP2 promoted the degradation of the RNA transcripts of the ATP6V1A gene, thereby impairing lysosomal function and resulting in a unique secretome that greatly enhances breast cancer cell invasiveness [20]. In addition to downregulation of target genes by increased RNA degradation, IGF2BP2 was shown to interact with N6-methyladenosine (m6A)-modified RNAs and enhance the stability of these RNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IGF2BP2 has been proposed as a tumor promoter and shown to affect many cancer hallmarks through positive or negative regulation of its target genes. A recent study demonstrated that IGF2BP2 promoted the degradation of the RNA transcripts of the ATP6V1A gene, thereby impairing lysosomal function and resulting in a unique secretome that greatly enhances breast cancer cell invasiveness [20]. In addition to downregulation of target genes by increased RNA degradation, IGF2BP2 was shown to interact with N6-methyladenosine (m6A)-modified RNAs and enhance the stability of these RNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, IGF2BP2 was shown to govern cancer metabolism, apoptosis, invasion, and metastasis by regulating different types of RNA species post-transcriptionally in numerous cell types and pathways [19]. Recently, an intriguing study reported that IGF2BP2 promoted the degradation of the RNA transcript encoding ATP6V1A, a catalytic subunit of the vacuolar ATPase, thus impairing lysosomal function and resulting in a unique secretome that greatly enhances breast cancer cell invasiveness [20]. Yet, as N6-methyladenosine modification of various RNA species has been implicated in regulating many aspects of OSCC biology [21][22][23], the involvement of IGF2BP2 in influencing oral cancer progression remains largely unclear.…”
Section: Ivyspringmentioning
confidence: 99%
“…However, recent studies have shown that IGF2BP2 is also an m6A reader. It contains four K-homologous structural domains and two RNA recognition motifs that can affect the post-transcriptional regulation of various genes [ 44 ]. Through communication with miRNAs, lncRNAs, mRNAs, and other m6A-related genes [ 20 ], it can regulate cellular metabolism and influence biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…IGF2BP2 is a unique member of the IGF2BPs family, exhibiting wide expression during embryonic development and in adult tissues, whereas IGF2BP1/3 expression is extremely low or absent postnatally (Bell et al 2013). Emerging evidence highlights the significant role of IGF2BP2 as an m 6 A reader in multiple physiological and pathological processes, particularly in the context of cancers and metabolic disorders (Dai 2020; Latifkar et al 2022). Interestingly, Wang et al innovatively elucidated the mechanism by which IGF2BP2 regulated macrophage polarization.…”
Section: Introductionmentioning
confidence: 99%